Phenolic Compounds: A Review of Their Possible Role as In Vivo Antioxidants of Wine - de Beer, D.; Joubert, E.; Gelderblom, W.C.A.; Manley, M. (South African Journal of Enology and Viticulture, 2017)
Phenolic compounds are a large and complex group of chemical constituents found in red and white wines which not only affect their quality, but also contribute to their beneficial health effects. The antioxidant properties of phenolic compounds are important in determining their role as protective agents against free radical-mediated disease processes. This review discusses the principles of oxidative stress and the resultant cellular damage caused by lipid peroxidation in vivo. Different groups of wine phenolic compounds are detailed, with specific reference to their in vitro antioxidant activity and their relative potency as free radical scavengers. The absorption and bioavailability of phenolic compounds from dietary sources is discussed.